Growth Performances and Growing Stock of Rattan in the Community Managed Forests of Nepal - Chowdhary, Chhote Lal; Dutta, I.C. (Journal of Advanced Academic Research, 2020)
Calamus tenuis Roxb, the economically potential rattan species, has been increasing in the community managed forests. Quantitative and qualitative information was collected in 2016 and 2017. The research was carried out in 20 Community Forest User Groups of Kailali and Bardiya district. Growing stock was measured using stratified random sampling in the community forests, followed by socio-economic information through semi-structured questionnaire to 526 respondentsincluding focus group discussions with executive member of community forest user groups. The study found that average growth of Calamus tenuis in the community forests was 0.85 cms per year, the maximum growth attained up to 2.5 meter per year if they get associated trees to climb on. It’ is a clumpy palm, producing 3-7 rhizomes in one year and reaches up to 25 rhizomes in 3-4 years period. There are 15 to 25percent immature culms in a clump with estimate the number of clumps per hectare in managed rattan forest are 200 to 500. Growing stock is estimated from 38,860 to 39,560 per hectare in the community forest comprising about 57 percent large size, 19 percent medium size and 24percent regeneration. The mean length was measured 5.80 meter and mean diameter 9.29 mm. Weight difference of rattan with and without leaf sheath is 25 percent, reduction in oven dry weight is 75.9 percent, and air dry weight is 32 percent. More than 20 CFUGs have produced natural rattan in the community forests of Kailali and Bardiya districts. By the number of CFUGs, Bardiya district has more than 19 CFUGs and Kailali district has one CFUG managing natural rattan. Total estimated production of rattan in both districts is over 250 metric ton. Harvesting is restricted due to limitation of provision of Initial Environment Examination (IEE). According to these conditions, CFUGs should have get approval the detail IEE. None of the CFUGS have prepared the IEE. In such a condition, CFUGs can only harvest less than five quintal (5000 kg) rattan as per approved FOP. The study concludes that despite site quality remains constant, the associated tree species to climb them are encouraging factor. Detail growing stock needs to be incorporated in the rattan management plan / forest operational plan to mainstream in the process.